High-efficient microwave-assisted method for the preparation of foamed liquid glass granules - Rimar, T.E.; Kryuchkova, E.Ju.; Pinchukova, N.A.; Voloshko, A.Y.; Chebanov, V.A. (Functional Materials, 2016)
In the present work, feasibility and efficiency of microwave-assisted preparation of the foam glass granules intended for production of the blocked heat-insulating materials were studied, and the effect of MW irradiation on the quality of the prepared foamed granules was assessed. The high quality material was obtained using microwave irradiation at much lower temperature in comparison with the known thermal method. The optimal process parameters were properly elaborated and analyzed.